ROLE OF CLINICAL PHARMACIST IN ASSESSMENT OF DRUG RELATED PROBLEMS OF CARDIO VASCULAR AGENTS IN DEPARTMENT OF CARDIOLOGY IN A TERTIARYCARE HOSPITAL – A PROSPECTIVE OBSERVATIONAL STUDY (World Journal of Current Medical and Pharmaceutical Research, 2019)
In total, of 173 prescriptions of the patient the total number of 329 drug interaction was found in which the 240 interaction was found in male and 89 in the female bearing the 72.90% and 27.10% respectively. Patient was of various age groups in which the maximum frequency was seen in the age group of 61- 70 years having 105 interaction bearing the percentage of 31.9% . According to the participation of different age group of the male and female with their corresponding age .The participation of male is high having frequency of 240 (72.9% )than female participation of frequency 89 (27.1%).The participation of male in the age group of 61-70 years is 83 and the female is 40 in the age group of 51-60 years. Potential drug interactions were categorized based on the gender. In that compared to 13 (40.6) females, males 19 (59.4%) were found to have more potential drug interactions. Our study more potential drug interactions in adult patients. Because, in adults lacking of nutrition’s and in elderly patients multiple prescribers, multiple drugs and multiple diseases. The number of potential DDI increased with an increase in the number of drug prescribed. The numbers of drug prescribed increase with age .This drug interaction have a potential to increase or decrease the therapeutic effect or to increase the risk of ADR. An increased awareness of PDDIs , rational co –prescription of drugs and a close monitoring of patients in whom these drugs are prescribed is recommended .The recommendation is based on the special monitoring and the perspiration of the clinical pharmacist .The Drug interaction observed in the geriatric patient are more severe and common in compared to the other group of study. The geriatric patient are physiological disability in correspond with the first pass metabolism and the presence of the other disease which also enables the multiple prescription causing poly pharmacy. The gender specification also the cause of the interaction , the female are more prone to the drug interaction due to the hormonal distribution in the body and inability of the physiological function to absorb and the distribution .The special training should be provided to the pharmacist for looking forward of the geriatric patient and female patient .The training regarding the prescription their adherence ,use ,toxicity , dosage regimen ,are being properly enabled in the training for the practical application . This study helps to know the different interaction related to the cardiovascular agent with own class of the drug and the other class of drugs used therapeutically to care the disease.